The Impact of Political Advertisements on Canadian Youth - Anstey, Hannah Jean (Université d'Ottawa | University of Ottawa, 2024)
Young Canadians have turned out to the ballot box less than older generations during recent elections; despite the fact that they are often highly educated and have access to rich political information in a hybrid and high-choice media system. Part of the explanation for this may be a lack of political efficacy. To better examine this problem, and the role of political efficacy in the Canadian political communications ecosystem, a mixed methods approach is used in this study including content analysis, data collection, and analysis of survey data to better understand the impacts of campaign communication, via video advertisements on Facebook, has on the political efficacy of Canadian youth. The findings show that political advertisements, writ large, do not impact political efficacy. However, certain advertisements included in the sample had measurable impacts on political efficacy, as well as emotionality and subjective credibility. Implications of these findings are important as campaigns continue to develop new tactics and strategies to better target their messaging during and outside of writ periods. Political communications practitioners can apply these findings to their work to more impactfully engage with Canada’s youngest electorate
Keywords: political advertisements; political efficacy; surveys; pre-test / post-test; democratic participation